Description of Student Anxiety in Facing Midterm Exams - Febrianti, Arly; Anggraini, Desy; Apriani, Dwi; Febrianti, Tri; Prautami, Erike Septa (Institute Of Computer Science (IOCS), 2024)
Anxiety is an unpleasant emotional state, in the form of a psychophysiological response that arises in anticipation of unreal danger. This condition is caused by an unknown intrapsychic conflict. Exams are one of the stressors that students often experience. This research aims to determine the level of student anxiety in facing the Mid-Semester Examination at STIKES Hesti Wira Sriwijaya. This research is descriptive research using the Accidental Sampling technique with a sample size of 83 respondents. Research results from 83 respondents. Most of them experienced mild anxiety, namely 54 respondents (65.06%). To reduce anxiety, students are expected to prepare themselves long before the exam is carried out by studying hard and also through group study activities